Menanam Padi: Kajian Pengambilan Keputusan Petani dalam Menentukan Varietas Padi - Semiarto Aji Purwanto (Antropologi Indonesia, 1998)
Rice farmers in Sidamukti, West Java plant several varieties of rice, sometimes planting twoor three varieties together in one plot of land. The decision to plant a specific variety is strongly influenced by farmers' agricultural knowledge, such as knowledge of varieties of rice, periods of maturation, tastes, characteristic of specific varieties, as well as knowledge of environmental conditions, including soil conditions, the need of fertilizer and seasonal changes. The author suggest that this knowledge, as a basis for decision making is at a pre-attentive stage that has become patterned, and its nearly or perhaps entirely out of conscious consideration. In fact, external situational factors operating at the start of planting play a dominant role in the decision to plant a specific variety of rice. A multitude of factors - such as pressure from village authorities to plant certain varieties in keeping with development programs; to supply of grain, fertilizers and water for irrigation; the desire to experiment, and the demands of landowners - often become significant determinants. The author arrives at the conclusion that studies of decision making processes that view knowledge systems as recipes or patterns for behavior must be supplemented by close observation and understanding the context and situation in which behavior is generated.